Human papillomavirus vaccine for cervical cancer prevention in India: new improvement and way forward - Sharma, Meenakshi; Kaur, Ekjot; Sandhu, Renu; Kaur, Samandeep (International Journal Of Community Medicine And Public Health, 2024)
Cervical cancer is the malignant abnormal changes in the tissues of cervix mostly transmitted through the human papilloma virus. Prophylactic vaccination against HPV is effective strategy to prevent cervical cancer. India has access to two types of vaccines that are licensed worldwide, the bivalent cervarix and the quadrivalent Gardasil. The drug controller general of India has authorized “CERVAVAC” a new HPV vaccination that is less expensive and is being offered in India as a single dose for females between the ages of 9 and 19 years. The government said in February 2024 that girls between the ages of 9 and 14 will receive the HPV vaccine as part of universal immunization programme. There are significant obstacles to vaccination implementation in India like lack of epidemiological evidences for illness prioritization, vaccine duration, parental attitude and vaccine acceptance. The WHO’s goal of eradicating cervical cancer by 2030 depends on implementing socially and culturally relevant public awareness campaigns after educational initiatives for healthcare professionals.